Infectious complications of hip arthroplasty: Causes and results of treatment - Pidhaietskyi, Vitalii M.; Gayko, Georgii V.; Kozak, Roman A.; Nizalov, Taras V. (International journal of health sciences, 2021)
The objective of the research is to study the causes and outcomes of infectious complications after total hip arthroplasty. The background of the research is for order carisoprodol buy soma online overnight delivery the analysis of outcomes of 364 patients with complications after total hip arthroplasty; 369 cases, from 2005 to 2018. The infectious complications accounted for 21.7% (80 cases). The work involves clinical, radiological, microbiological, and statistical research methods. As a result of research causes of suppurative complications after total hip arthroplasty were: chronic infectious diseases of internal organs (t=3.37, p=0.001), instability of prosthetic components (t=3.14, p=0.002), over two previous surgical interventions involving the affected joint (t=2.43, p=0.005). In the treatment of periprosthetic infections, sanitizing interventions without the prosthetic components’ removal appeared efficient within only up to 3 weeks. If the sanitizing interventions were inconclusive, the double-stage revision prosthetics appeared adequate in a reliable number of cases (t = 11.2, p = 0.0028), namely 24, which amounted to 92.3%. In conclusion, it was concluded that the causes of periprosthetic infections were: diseases of the internal organs, instability of the components, over two surgical operations involving the same joint. The development of various complications after order carisoprodol total hip replacements demands surgical revision procedures.